Adapting pharmacy experiential education during COVID-19: Innovating remote preceptor resources, tools, and patient care delivery beyond virtual meetings. (5th May 2021) - Law, Elaine; Scott, Marie C; Moon, Yong S K; Lee, Audrey J; Bandy, Veronica T; Haydon, Andrew; Shek, Allen; Kang-Birken, S Lena
Abstract: Purpose: To describe the innovative teaching practices, tools, and resources for remote learning developed by a school of pharmacy with a decentralized experiential program to empower and support preceptors in response to the coronavirus disease 2019 (COVID-19) pandemic. Summary: As the pandemic has continued, there have been significant shifts in pharmacy workflow, staffing, and patient care delivery. Pharmacy students are slowly being reintegrated into these learning environments. Although preceptors are willing and eager to teach, many lack the resources, tools, and support to create remote learning experiences at their facilities. The University of the Pacific Thomas J. Long School of Pharmacy has a decentralized experiential education model in which faculty regional coordinators with clinical practices and diverse expertise are disseminated throughout California. This model allowed us to collaborate and understand preceptor needs from a local level. We created a preceptor COVID-19 guidance document, introduced innovative virtual playbooks to pivot up to 100% remote rotations, and promoted the layered learning model to integrate pharmacy residents into the remote teaching space. Communication and flexibility are key to ensure student and preceptor safety while maintaining high-quality advanced pharmacy practice experiences and preserving patient-student relationships in telehealth. Conclusion: Overall, we successfully created innovative solutions and leveraged our decentralized experiential model to meet the teaching and learning demands during an unanticipated crisis. We continue to adapt and plan to assess the effectiveness of the tools by administering surveys of preceptors and pharmacy students.